INFRARED PHOTOMETRY FOR STARS IN THE HYADES MAIN SEQUENCE - IRIARTE ERRO, B (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1969)
Taking into account that the Hyades main sequence stars have been used as "standard" stars and provide the basis of comparison with other objects we have obtained infrared colors for them with great precision.
BOL OBS TONAN TACUB
Keywords: INFRARED PHOTOMETRY, STARS, HYADES, MAIN SEQUENCE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS